Ø£ÙÙÙØ§Ù Ø¹Ù Ø§ÙØ¨Ø¯ÙØ¹ : ØªØ§Ø±ÙØ®Ù ÙØ£ÙØ³Ø§Ù Ù - Faqihudin, Didin (Institut Agama Islam Negeri (IAIN) Palu, 2007)
This articleÂ deals with one aspect of balaghah i.e. badiâ. As we know badiâ is a science by which we know some beautiful features of sentences. But howÂ badiâ emerged in the history of Arabic culture? Who is responsible for the rising ofÂ badiâ? And how many partsÂ badiâ has? This articleÂ tries to answer these questions.Â Kata Kunci : âilm al-badiâ,âilm al-balagah, âilm al-bayan,âilm al- maâani